Valuation of Reliability Index in Distribution Network 13.8 kV - F. Yaser; Azriyenni Azhari Zakri; D. Y. Sukma (JOURNAL OF SCIENCE AND APPLIED ENGINEERING, 2020)
This study is proposed to calculate and analyze the level of reliability of the 13.8 kV distribution system. To calculate the reliability index based on the reliability index of the value of the failure that occurred. The method used throughout this study is the Reliability Index Assessment (RIA) when this method takes into account momentary interruption. The distribution network is considered as the object of this study has six feeders. Based on blackout data obtained, the reliability index becomes smaller and can be distinguished between permanent and temporary disruptions. The calculation results show the reliability index of SAIDI, SAIDI, and MAIFI based on the type of disturbance; the results of this calculation will be compared with SPLN and IEEE. A comparison of the results of the calculation of SAIFI values from the six feeders analyzed all meet the SPLN and IEEE rules. However, in one of the feeders, the SAIDI index exceeds the established standard, which is 24 hours/year/customer, with the SPLN regulation being 21 hours/year/customer, and the IEEE standard is 2.3 hours/customer/year. And finally, the results of an analysis of the MAIFI index for all feeders meet the IEEE standard of 5 times/year/customers.